(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
The detention of prisoners which aims at providing them opportunities to undergo the process of rehabilitation in public prisons across the country has raised certain issues. This includes the question of whether their rights provided under the law are in conformity with the high intent of law (maqasid al-shariah). Likewise, the issue of whether the legislation complies with the guidelines prescribed by international regulations or instruments. Thus, a study was conducted at a public prison through interview and observation. The research involved 25 of women prisoners, eight prison officers, and a Superintendent of Kajang women’s prison. The study finds that in general, the provisions of law relating to prisons and the supervision of inmates under the Prisons Act and Prison Regulations adhere to the high intent of law and international standards. Nevertheless, there are minor issues that need to be addressed in order to ensure that the objective of rehabilitation is successfully met. As such, The Malaysian Prisons Department is urged to observe the principles of Islamic law, provisions of international conventions as long as these are in tandem with Islamic principles and local laws, apart from the best practices in other countries including other Muslim countries. This is to ensure that the prisoners’ welfare and specific needs, particularly those of women prisoners, are fulfilled. In other words, international law, to a certain extent, and Islamic law should be the benchmarks for possible future improvement. Keywords: prisoners, rehabilitation, prison, women, maqasid